Dry matter analysis in cover crops under the effect of straw in the “cerrado” (Brazilian Savanna) and phytosociology of the weed community (Revista de Ciências Agroveterinárias, 2013)
The population control of weeds with the use of cover crops is common practice and can be promoted during the vegetative growth of the sown crop or after its desiccation. The objective of this paper was to determine the dry matter yield of cover crops sown at different times in the Cerrado region and identify the floristic composition of the weed community present in this production area. The experiment was conducted in field conditions in Selvíria, MS, with a randomized block design with 10 treatments and four cover crops: sorghum, sunnhemp, millet, pasture and fallow area, and two sowing dates, March 27th, 2008 and April 23th, 2008. Dry matter yield was collected on July 07th 2008. The characterization and phytosociological study of the weed community was held on October 20th, 2008. Nineteen species of weed were identified in the cover. The results showed that the pasture (Brachiaria brizantha) under heavy rainfall and high temperatures produced large areas of dry matter within a short period of time. Thus, the cover crops are able to reduce the weed population and the fallow area gets infested quickly and can compete directly with crops in succession.
Keywords: Cover crops; Phyto-sociological study; Weed; Importance value; Crop rotation.